2020
DOI: 10.1002/dc.24484
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of cytology smears and cell block in adrenal lesions

Abstract: Background: Cytology of the adrenal gland is a less performed technique even in tertiary care centres; yet cytological evaluation is an important diagnostic tool for assessment of adrenal lesions. Our objective was to evaluate the diagnostic utility of FNAC smears and cellblock with immunohistochemistry (IHC) in lesions of the adrenal. Material and methods: We had a total of 50 cases over a period of 2 years where both FNAC smears and cellblocks were taken. The smears and cellblocks were examined for adequacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Microscopic examination of the CB section can successfully categorise HB into embryonal and foetal subtype. Different studies have shown prognostic significance of this categorisation on FNAC/CB with pure foetal type having the best outcome 17 . Immuno‐reactivity for beta‐catenin was seen in all cases of HB and foetal types showed extensive PAS positivity 18 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Microscopic examination of the CB section can successfully categorise HB into embryonal and foetal subtype. Different studies have shown prognostic significance of this categorisation on FNAC/CB with pure foetal type having the best outcome 17 . Immuno‐reactivity for beta‐catenin was seen in all cases of HB and foetal types showed extensive PAS positivity 18 .…”
Section: Discussionmentioning
confidence: 89%
“…However, reliably distinguishing ACC from ACA is difficult on FNAC and CB in absence of capsular and vascular invasion. These become even more difficult in paediatric patients where cytological features alone are not an adequate guide in favour of malignancy 14‐17 …”
Section: Discussionmentioning
confidence: 99%
“…With the advent of new imaging modalities and the widespread use of imaging studies, the detection rate of adrenal nodules has increased enormously. Most of these lesions are detected during a staging workup for cancer elsewhere or for other complaints unrelated to the adrenal gland, often referred to as “incidentalomas.” 1–3 There are a number of etiologies giving rise to adrenal nodules including adrenal cortical adenoma, adrenal cortical carcinoma, pheochromocytoma, myelolipoma, and metastatic lesions. In patients with an adrenal mass and an extra‐adrenal malignancy, the frequency of this mass being metastatic can range from 32% to 73% 3 …”
Section: Introductionmentioning
confidence: 99%